Sekolah Hijau, Anak Sehat: Program Penghijauan dan Pendidikan Hidup Sehat SDN Curahdami 3 - Fajar Mumtaz Muhyiddin; Wazirul Ihsan Rizky Ramadhan; Mochammad Syafril Adriansyah; Ahmad Rizal Wahyudi; Silvina Alifiani; Ahmad Divo Miftahul Arifin; Agung Supriono; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Education plays a vital role in shaping students' character, morals, and knowledge, particularly in fostering environmental awareness. However, current conditions indicate that many school environments remain poorly maintained due to low student awareness. Community service activities at SDN Curahdami 3 aimed to instill healthy living habits from an early age in order to create a safe and harmonious school environment. The program was implemented through three meetings (September 26–October 10, 2025) involving students in grades 4, 5, and 6, using descriptive methods with audio-visual media along with classroom and field practices. The results showed an overall improvement of approximately 50%, reflecting increased student understanding and positive behavioral changes in environmental stewardship and healthy lifestyles. Students became more cooperative, hygienic, and inclined to choose nutritious foods. Healthy living education proved effective in cultivating empathy, solidarity, and care for the surrounding environment.